Pengaruh Citra Toko dan Persepsi Harga Terhadap Niat Beli Ulang dengan Citra Produk Private Label Sebagai Variabel Mediasi (Studi Empiris pada Hypermart dan Indomaret di Kota Pontianak) - Rony Jusfarani B2042171020 (Equator Journal of Management and Entrepreneurship (EJME), 2020)
Repurchase intention is an important factor for the company. The intention to repurchase a product arises because consumers are satisfied with the product they bought before. The purpose of this study was to determine the effect of Store image, Price perception and Private label product image to Repurchase intention on Hypermart and Indomaret Pontianak City. Data collection was carried out by distributing questionnaires containing statements with the number of respondents as many as 60 people on Hypermart and 60 people on Indomaret. The sampling technique uses the non-probability sampling method in the form of purposive sampling. Data from the results of questionnaire collection are processed using validity, reliability, classic assumption and path analysis.The results showed: 1) Store image and price perception has a significantly effect to private label product image on Hypermart customers. 2) Store image and price perception has a significantly effect to repurchase intention on Hypermart customers. 3) Private label product image has a significantly effect to repurchase intention on Hypermart customers. 4) Store image and price perception has a significantly effect to private label product image on Indomaret customers. 5) Store image and price perception has a significantly effect to repurchase intention on Indomaret customers. 6) Private label product image has no significantly effect to repurchase intention on Indomaret customers.